Determination of Soil Fluorine Speciation and Main Factors Affecting Tea Fluorine Content in Tea Gardens of Daba Mountain - Boxin FENG; Qianni MEN; Liming GAN; Liyong WEI; Jiufen LIU; Tao HE; Peng WANG; Yixin HE (Yankuang ceshi)
In recent years, the relationship between fluorine intake through tea drinking and human health has received significant attention. To investigate the effect of soil properties on tea fluorine, 64 sets of tea garden soil-tea samples were collected in Ziyang County, Daba Mountain area, and a Freundlich model that affects the fluorine content of tea was established. The results show that：(1) The fluorine content in the surface soil of tea gardens ranges from 487.37 to 1120.78mg/kg, with an average value of 730.63mg/kg; The fluorine content of tea is 31.23-112.49mg/kg, with an average value of 57.58mg/kg. All samples do not exceed the limit of agricultural standards (NY659—2003); (2) The distribution of fluorine speciation in the soil is as follows: residual state>water-soluble state>organic state>iron manganese bound state>exchangeable state; (3) A multiple regression equation affecting the fluorine content in tea was constructed using five factors: water-soluble fluorine, CEC, exchangeable aluminum, organic matter, and pH as variables. The model can explain 86.0% of the variation, and the prediction accuracy of the model reached 88.0% through validation. This study can provide theoretical basis for the development of green agriculture. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202307070089.